Efficacy of bioactive materials in preventing Streptococcus mutans-induced caries on enamel and dentine - Contreras, Sheila Mondragón [UNESP]; Fernandes, Juliana Benace [UNESP]; Spinola, Manuela da Silva; Garcia, Maíra Terra [UNESP]; Junqueira, Juliana Campos [UNESP]; Bresciani, Eduardo [UNESP]; Caneppele, Taciana Marco Ferraz [UNESP] (Wiley, 2023)
The study investigated the ability of bioactive materials used to restore enamel and dentine specimens to prevent caries. Enamel (n = 50) and dentine (n = 50) specimens were obtained from bovine incisors, prepared, and randomly allocated to one of five groups according to the restorative treatment: alkasite without adhesive system; alkasite with adhesive system; high viscosity glass ionomer cement; resin composite; no restoration; negative control group. Specimens were restored, exposed to a thermal cycling aging protocol, sterilized, and exposed to a cariogenic challenge induced by Streptococcus mutans and then submitted to surface and subsurface microhardness tests and polarized light microscopy to verify the caries lesion development in enamel or dentine surrounding the restorative materials. Data were analyzed using one-way ANOVA. In enamel and dentine, glass ionomer cement, alkasite without and with adhesive system presented a lower percentage surface microhardness loss than resin composite and negative control. Enamel subsurface microhardness presented no statistically significant differences between glass ionomer cement, alkasite without and with adhesive system. Glass ionomer cement also did not present statistically significant differences from resin composite and the negative control. In dentine, glass ionomer cement showed the highest subsurface microhardness values. In conclusion, bioactive restorative materials provide greater protection to enamel and dentine against surface caries development than resin composite.
Keywords: alkasite; dental caries; glass ionomer cements; resin composites